Batman vs. Robin - Oliva, Jay; O'Mara, Jason; McCallum, David, 1933-2023; Sisto, Jeremy, 1974-; Kane, Bob (Burbank, CA : Warner Bros. Entertainment, 2015)
After meeting the mysterious Talon and his Court of Owls, Batman and Robin discover that they have started to see each other as dangerous adversaries.
Originally released directly to video in 2015.
"DC Universe original movie"--Container.
Based on characters created by Bob Kane.
Dolby digital 5.1, anamorphic wide screen 1.77:1.
Features: sneak peek at Justice League : gods & monsters.
Voices: Jason O'Mara, David McCallum, Jeremy Sisto, Grey DeLisle, Kevin Conroy.
Keywords: Batman (Fictitious character) -- Drama; Superheroes -- Drama; Good and evil -- Drama; Fiction films; Video recordings for the hearing impaired; Feature films; Animated films; Superhero films